The dying Sahara US imperialism and terror in Africa - Keenan, Jeremy (London Pluto Press, 2013)
In The Dark Sahara (Pluto, 2009), Jeremy Keenan exposed the collusion between the US and Algeria in fabricating terrorism to justify a new ?Saharan front? in Washington?s War on Terror. Now, in The Dying Sahara, he reveals how the designation of the region as a ?Terror Zone? has destroyed the lives and livelihoods of thousands of innocent people.
Includes bibliographical references (pages 283-312) and index.
Keywords: Terrorism--Sahara.